2017
DOI: 10.1097/acm.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Medical Records, Medical Students, and Ambulatory Family Physicians: A Multi-Institution Study

Abstract: Ambulatory medical student training in the use of EMRs not only varies but also requires many preceptors to break rules for students to learn important documentation skills. Without changes to the policies surrounding student access to and use of EMRs, future physicians will enter residency without the training they need to appropriately document patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…A possible solution of this issue is providing feedback to medical students after documentation which enhance documentation skills [ 38 ]. This finding also explained why most medical students who have access to medical records use seniors’ accounts, which also mentioned by other study [ 39 ]. Beside liability concerns, other studies mentioned other barriers such as billing, reduced productivity, financial concerns, and logistical and structural problems [ 3 , 6 , 18 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A possible solution of this issue is providing feedback to medical students after documentation which enhance documentation skills [ 38 ]. This finding also explained why most medical students who have access to medical records use seniors’ accounts, which also mentioned by other study [ 39 ]. Beside liability concerns, other studies mentioned other barriers such as billing, reduced productivity, financial concerns, and logistical and structural problems [ 3 , 6 , 18 ].…”
Section: Discussionsupporting
confidence: 78%
“…This finding also explained why most medical students who have access to medical records use seniors' Fig. 3 Participants' preference for the type of medical record they want to use in their future practice accounts, which also mentioned by other study [39]. Beside liability concerns, other studies mentioned other barriers such as billing, reduced productivity, financial concerns, and logistical and structural problems [3,6,18].…”
Section: Discussionmentioning
confidence: 57%
“…Many of them have shown that most students access EHRs while they are in medical school. [4][5][6][7][8][9][10] This is not surprising given the widespread use of EHR systems in clinical settings and calls to incorporate instruction in EHR competencies early in a physician's education. Studies also suggest, however, that some medical students receive limited opportunities to enter information, including notes and orders, into patient records in EHRs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also suggest, however, that some medical students receive limited opportunities to enter information, including notes and orders, into patient records in EHRs. [4][5][6][7][8][9][10] This tends to occur despite their ability to access them generally.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of medical and nursing student placements show significant variability across settings in the types and volume of documentation performed by students into eMRs. [8][9][10][11][12][13] Organizational policies regarding student eMR access also vary across placement sites. 14 Several barriers to student eMR access and documentation have been identified, including, for example, university and hospital policies and processes, concerns about medical liability, and logistical issues (e.g., training and access).…”
Section: Background and Significancementioning
confidence: 99%